An After Effect Of Sorafenib Therapy- A Case Report (Journal of Pharmaceutical Negative Results, 2022)
Sorafenib, a multikinase inhibitor, is FDA approved for the treatment of hepatocellular carcinoma (HCC), renal cell carcinoma (RCC) and thyroid carcinoma. Various adverse effects have been documented in patients taking standard sorafenib therapy. Out of which, hand-foot skin reaction (HFSR) is the most common cutaneous toxicity. Hand foot skin reaction presents with hyperkeratotic lesions with superficial blisters surrounded by peripheral erythema. It commonly affects the flexural surfaces of the digits and the pressure areas of palms and soles. The cutaneous side effects are dose dependent and are reported to occur in patients who are on a standard dose of 400 mg twice daily or more. But in our patient, it developed at a low dose (200 mg twice daily). Sorafenib-induced HFSR, though a dose dependent reversible reaction, has a significant impact on the quality of life. Hence prompt diagnosis and management at the earliest, can reduce the morbidity.